Readmission Rate, Predictors, Outcomes, and Burden of Readmission of Hepatorenal Syndrome in the United States: A Nationwide Analysis - Abdullah Sohail; Ammad J. Chaudhary; Muhammad Mujtaba Bhinder; Khadija Zahid; Kyle Brown (JGH Open)
ABSTRACT Background Nationwide US data on readmission rates for patients with cirrhosis admitted with hepatorenal syndrome (HRS) is lacking. We reviewed 30‐day readmission rates after HRS‐related hospitalizations, the associated predictors of readmissions, and their impact on resource utilization and mortality in the United States. Methods We identified all adults admitted with HRS between 2016 and 2019 using the Nationwide Readmission database of the Agency for Healthcare Research and Quality's Healthcare Cost and Utilization Project. The primary outcome was all‐cause 30‐day readmission rate. Secondary outcomes were inpatient mortality rate, predictors of readmission, and resource utilization. Results We identified 245 850 hospitalizations of patients admitted for HRS in the United States from 2016 to 2019. Of these, 214 890 met the inclusion criteria. Mean age was 59.16 years, and 61.31% were males. Medicare was the most common primary payer (44.82%) followed by Medicaid (25.58%). The readmission rate was 24.6% within 30 days of discharge from index hospitalization. The most common cause of readmission was alcoholic cirrhosis with ascites (14.87%), followed by sepsis (9.32%) and unspecified hepatic failure (9%). The in‐hospital mortality rate for index hospitalization was 29.52% and 14.35% among those readmitted within 30 days. The mean length of stay (12.33 days vs. 7.15 days, p < 0.01) and hospitalization costs ($44 903 vs. $22 353, p < 0.01) were higher for index hospitalizations than readmissions. Conclusions Our study demonstrated that all‐cause 30‐day readmission and in‐hospital mortality rates after the development of HRS were strikingly high. This warrants health policies and interventions at the institutional level, including close post‐hospital discharge follow‐up, to decrease readmission rates, improve patient outcomes, and reduce cost burden.